2022
DOI: 10.48550/arxiv.2203.09448
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A note on character sums over short moving intervals

Abstract: We investigate the sums (1/ √ H) X 0. On the other hand, we show it is tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Thus, there is no paucity phenomenon in the linear case and our mild condition is necessary. However, we remark that in the companion paper [19] of the authors and Pandey, the analogous counting problem is solved for 𝑃(𝑥) = 𝑥 with short interval support [𝑁, 𝑁 + 𝐻], 𝐻 ⩽ 𝑁∕(log 𝑁) 𝐶𝑘 2 , 1 and this is one of the key steps in making progress toward a recent question of Harper [10]. The "paucity" in this case comes from the "shortness" of the interval; in comparison, the "paucity" in the present paper comes from the fact that 𝑃(𝑥) is "genuinely of degree ⩾ 2" (i.e., it has at least two distinct complex roots).…”
Section: Linear Case and Optimality Of The Resultsmentioning
confidence: 99%
“…Thus, there is no paucity phenomenon in the linear case and our mild condition is necessary. However, we remark that in the companion paper [19] of the authors and Pandey, the analogous counting problem is solved for 𝑃(𝑥) = 𝑥 with short interval support [𝑁, 𝑁 + 𝐻], 𝐻 ⩽ 𝑁∕(log 𝑁) 𝐶𝑘 2 , 1 and this is one of the key steps in making progress toward a recent question of Harper [10]. The "paucity" in this case comes from the "shortness" of the interval; in comparison, the "paucity" in the present paper comes from the fact that 𝑃(𝑥) is "genuinely of degree ⩾ 2" (i.e., it has at least two distinct complex roots).…”
Section: Linear Case and Optimality Of The Resultsmentioning
confidence: 99%
“…, p − 1}, the short sum S p (x + H) − S p (x) tends to a normal distribution with mean zero and variance H, provided log H = o(log p) and H → ∞ as p → ∞. Recently, Harper [12] showed that this is no longer the case if H is much larger, namely when H ⩾ p/(log p) A , and A > 0 is a fixed constant.…”
Section: Introductionmentioning
confidence: 99%
“…However, we remark that in the companion paper [15] of the authors and Pandey, the analogous counting problem is solved for P (x) = x with short interval support [N, N +H], H ≤ N/(log N) Ck 2 , 1 and this is one of the key steps in making progress towards a recent question of Harper [7]. The "paucity" in the linear case comes from the "shortness" of the interval; in comparison, the "paucity" in the present paper comes from the fact that P (x) is "genuinely of degree ≥ 2" (i.e.…”
Section: Introductionmentioning
confidence: 99%